Realtime local navigation for the blind: detection of lateral doors and sound interface - Moreno, M. (2013)
Worldwide there are about 285 million visually impaired persons, of which 39 million are blind and the others have low vision. Almost all systems designed to assist them are quite complex and expensive, but most blind persons do not have advanced technical assistance and they are rather poor. We are therefore developing a low-cost navigation aid which can be afforded by almost all blind persons: basically, the ultimate goal is to use only a mobile phone with a built-in camera. This aid complements the white cane, it is easily portable, and it is not a hindrance when walking with the cane. The system will have an easy and intuitive interface, yet providing assistance in local and global navigation in realtime. In this paper we present the progress concerning local navigation. Path and obstacle detection just beyond the reach of the cane is now supplemented by detection of doors in corridors. This is necessary for localization, i.e., for developing a better impression of the environment and for finding a specific room. A sophisticated sound interface can assist the user for centering on paths like sidewalks and corridors, alerting to looming obstacles for avoiding them.